Slow-wave sleep as a key player in offline memory processing: insights from human EEG studies - Keeble, Leanna; Monaghan, Padraic; Robertson, Edwin M.; Hannan, Sana (Frontiers in Behavioral Neuroscience, 2025)
Slow-wave sleep (SWS) plays a pivotal role in memory consolidation, and electroencephalography (EEG) has provided critical insights into the neural mechanisms underlying these processes. In this mini-review, we discuss how SWS supports the processing of both declarative and procedural memory, in addition to higher cognitive functioning. We focus on the latest evidence from human EEG studies that examine temporal regularities alongside those that have demonstrated the coordinated interplay between slow oscillations, sleep spindles, and hippocampal ripples. We discuss how the precise temporal coupling of these oscillatory events facilitates memory transfer from the hippocampus to the neocortex, enhancing neuronal reactivation and optimizing long-term memory consolidation. We also examine how disruptions to SWS—due to lifestyle factors, ageing, neurological disorders, or pharmacological agents—can impair slow-wave activity and spindle dynamics, leading to memory deficits. Further, we highlight emerging neuromodulation techniques, such as transcranial direct current stimulation and closed-loop auditory stimulation, which harness EEG-based insights to enhance SWS and improve memory outcomes. These findings collectively demonstrate the potential of integrating EEG methodologies with targeted therapeutic interventions to restore SWS, optimize memory consolidation and enhance cognitive health. Finally, we recommend directions for future research aimed at refining these approaches, evaluating their long-term efficacy across diverse populations, and exploring new strategies to preserve memory function in the context of healthy ageing and neurological disease.